2018
DOI: 10.1080/15384101.2018.1489175
|View full text |Cite
|
Sign up to set email alerts
|

The role of SAGA coactivator complex in snRNA transcription

Abstract: The general snRNA gene transcription apparatus has been extensively studied. However, the role of coactivators in this process is far from being clearly understood. Here, we have demonstrated that the Drosophila SAGA complex interacts with the PBP complex, the key component of the snRNA gene transcription apparatus, and is present at the promoter regions of the snRNA genes transcribed by both the RNA polymerase II and RNA polymerase III (U6 snRNA). We show that SAGA interacts with the Brf1 transcription factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Our results are in agreement with the data that the DUB module has both SAGA-related and independent functions. In summary, it can be argued that the SAGA complex in metazoans is widely involved in the regulation of gene transcription (Popova et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Our results are in agreement with the data that the DUB module has both SAGA-related and independent functions. In summary, it can be argued that the SAGA complex in metazoans is widely involved in the regulation of gene transcription (Popova et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Antibodies to Sgf11, ENY2, and Gcn5, available in our laboratory, were used in chromatin immunoprecipitation reactions. Since it was previously shown that the SAGA and DUB module are present on the promoters of both Pol II and Pol III dependent genes, we assessed the presence of factors on the promoter of the hsp70 gene (Pol IIdependent gene) in heat shock and on Pol III targets, the presence of SAGA in which has been shown previously [18,35].…”
Section: Analysis Of the Influence Of Proteins Of The Saga Complex On The Recruitment Of The Dub-module To The Promoter Region Of Saga-dementioning
confidence: 99%
“…Recently, SAGA was found to be involved in the transcription of small nuclear RNA (snRNA) genes in both Pol II-and Pol III-dependent [18]. Pol III transcribes a set of noncoding RNAs, including tRNA, 5S RNA, and U6 snRNA [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAGA-mediated chromatin modifications are important for expression of nearly all genes ( 5 , 6 ). The role of SAGA extends beyond transcription and includes mRNA export ( 7 , 8 ), mRNA splicing ( 8 ), RNA polymerase II- and III-dependent snRNA transcription ( 9 ), and DNA repair ( 10 , 11 ). SAGA is also important for development in metazoans ( 12 ) and tolerance of plants to environmental stress ( 13 ).…”
mentioning
confidence: 99%